Quantitative assessment and bioactivity of a periphytic biofilm from fish farming - Silva, Jéssica Lucinda Saldanha da; Torres Rodríguez, Marina Teresa; Carvalho , Fátima Cristiane Teles de; Sousa, Oscarina Viana de (Revista de Ciências Agroveterinárias, 2021)
The objective of this work was to quantitatively analyze the cultivable microbiota in isolated periphyton of tilapia cultivation tanks with later prospecting for bioactive substances produced in the biofilm and resistance to the action of antibiotics. The standard plate counting method using the pour plate technique was used to quantify the cultivable heterotrophic bacteria (CHB) and the spread plate technique for fungi. The production of antimicrobial substances by the community and the susceptibility to broad-spectrum antibiotics were investigated, both through the agar diffusion technique. The periphyton sample showed 1.73x106 CFU/mL in relation to the count of total cultivable heterotrophic bacteria and 1.45x102 CFU/mL relative to the density of fungi. The periphytic biofilm showed antibacterial action against Gram-positive bacteria. The antibiotics chloramphenicol, tetracycline, and cephalothin were effective against the biofilm components. However, the community showed a profile of resistance to imipenem. Bacteria are the dominant components in periphytic biofilm compared to fungi, contributing to nutrient cycling and influencing the quality of cultivated water. Periphyton has biotechnological potential for antimicrobial action.